Classification of patients with embolic stroke of undetermined source into cardioembolic and non‐cardioembolic profile subgroups. (25th April 2022) - Martin, Max Christian; Sichtermann, Thorsten; Schürmann, Kolja; Habib, Pardes; Wiesmann, Martin; Schulz, Jörg B.; Nikoubashman, Omid; Pinho, João; Reich, Arno
Abstract: Background and purpose: It is currently thought that embolic stroke of undetermined source (ESUS) has diverse underlying hidden etiologies, of which cardioembolism is one of the most important. The subgroup of patients with this etiology could theoretically benefit from oral anticoagulation, but it remains unclear if these patients can be correctly identified from other ESUS subgroups and which markers should be used. We aimed to determine whether a machine‐learning (ML) model could discriminate between ESUS patients with cardioembolic and those with non‐cardioembolic profiles using baseline demographic and laboratory variables. Methods: Based on a prospective registry of consecutive ischemic stroke patients submitted to acute revascularization therapies, an ML model was trained using the age, sex and 11 selected baseline laboratory parameters of patients with known stroke etiology, with the aim of correctly identifying patients with cardioembolic and non‐cardioembolic etiologies. The resulting model was used to classify ESUS patients into those with cardioembolic and those with non‐cardioembolic profiles. Results: The ML model was able to distinguish patients with known stroke etiology into cardioembolic or non‐cardioembolic profile groups with excellent accuracy (area under the curve = 0.82). When applied to ESUS patients, the model classified 40.3% as having cardioembolic profiles. ESUS patients with cardioembolic profiles were older, more frequently female, more frequently had hypertension, less frequently were active smokers, had higher CHA2 DS2 ‐VASc (Congestive heart failure or left ventricular systolic dysfunction, Hypertension, Age ≥ 75 [doubled], Diabetes, Stroke/transient ischemic attack [doubled], Vascular disease, Age 65–74, and Sex category) scores, and had more premature atrial complexes per hour. Conclusions: An ML model based on baseline demographic and laboratory variables was able to classify ESUS patients into cardioembolic or non‐cardioembolic profile groups and predicted that 40% of the ESUS patients had a cardioembolic profile. Abstract : Based on a prospective registry of 448 ischemic stroke patients, we trained 18 different machine‐learning (ML) models using data on age, sex and 11 selected baseline laboratory variables of patients with known stroke etiology. Thereby, the ML models were trained with the aim of correctly identifying patients with cardioembolic and non‐cardioembolic etiologies. Finally, the best performing model, the CatBoost Classifier, was applied to classify ESUS patients into cardioembolic or non‐cardioembolic profile subgroups and predicted that 40% of ESUS patients would have a cardioembolic profile.